2015
DOI: 10.1007/s13595-015-0489-2
|View full text |Cite
|
Sign up to set email alerts
|

Exceedance of critical loads and of critical limits impacts tree nutrition across Europe

Abstract: International audienceAbstractKey messageExceedance of critical limits in soil solution samples was more frequent in intensively monitored forest plots across Europe with critical loads for acidity and eutrophication exceeded compared to other plots from the same network. Elevated inorganic nitrogen concentrations in soil solution tended to be related to less favourable nutritional status.ContextForests have been exposed to elevated atmospheric deposition of acidifying and eutrophying sulphur and nitrogen comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 24 publications
(23 reference statements)
0
29
1
Order By: Relevance
“…Waldner et al (2014) considered further reductions as necessary to reduce N deposition to levels below which significant harmful effects do not occur in forests according to present knowledge. Such critical loads for organic N were exceeded on about 30-50% of 201 ICP Forests Level II forest plots as well as of 43 sites within the Swedish Throughfall Monitoring Network (Waldner et al 2015). These findings and the results presented in the article at hand suggest complementing forest ecosystem monitoring and assessments by using spatially high resolved long-term moss survey data, for indicating exposure in terms of HM and N atmospheric deposition and accumulation.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Waldner et al (2014) considered further reductions as necessary to reduce N deposition to levels below which significant harmful effects do not occur in forests according to present knowledge. Such critical loads for organic N were exceeded on about 30-50% of 201 ICP Forests Level II forest plots as well as of 43 sites within the Swedish Throughfall Monitoring Network (Waldner et al 2015). These findings and the results presented in the article at hand suggest complementing forest ecosystem monitoring and assessments by using spatially high resolved long-term moss survey data, for indicating exposure in terms of HM and N atmospheric deposition and accumulation.…”
mentioning
confidence: 56%
“…Thus, for the correlation analyses not only the moss measurement values were used but also surface estimations derived from them by kriging. The correlations indicated that the organisms used fairly well indicate atmospheric deposition and, therefore, should be used to enhance the spatial resolution of deposition maps and, subsequently, HM and N critical loads (ARGE StickstoffBW 2014; de Vries and Groenenberg 2009; Giordani et al 2014;Lorenz et al 2008;Lorenz and Granke 2009;Reinds and de Vries 2010;Waldner et al 2015). The latter are, among others, required for assessing and mapping ecosystem conditions.…”
Section: Discussionmentioning
confidence: 97%
“…Results from N deposition measurements across Europe confirm our findings -there is a slight decrease in N deposition, but critical deposition loads for nutrient N are exceeded in more than half of the monitoring plots in Europe (Seidling et al 2014). Critical loads for inorganic N deposition were exceeded on about a third to a half of the monitored forest plots of the ICP Forests Level II network across Europe (Waldner et al 2015). Elevated inorganic N concentrations in soil solution occurred more frequently in these plots (Waldner et al 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Elevated inorganic N concentrations in soil solution occurred more frequently in these plots (Waldner et al 2015). Indications of nutrient imbalances, such as low magnesium concentration in foliage or discoloration of needles and leaves, were rare but appeared more frequently on plots where the critical limits for soil solution were exceeded (Waldner et al 2015). Also in the Czech Republic there are regions where elevated N concentration in soil leads to nutrient imbalance, especially between N and phosphorus and N and magnesium (Lomský et al 2011(Lomský et al , 2012.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation